Developing Skills and Confidence in Non-Formal Education - Sullivan, Kevin (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Computer Science, 2022)
There is a growing recognition of the value of 21st century (21C) skills for modern learners, and many education systems are seeking to employ strategies to help their students develop those skills. This push is based on the idea that for students to thrive in a world where technology is developing rapidly and the ways in which we interact with people and information are constantly changing, they must develop relevant knowledge, skills, and confidence (Ravitz, Hixson, English, & Mergendoller, 2012). To help students acquire and improve these competencies, education systems must develop appropriate strategies and understand how to implement them for their students benefit. The development and validation of approaches and interventions that have a meaningful and sustained impact on students skills and confidence are a vital step in the ongoing reform of modern education systems. 21C teaching and learning refers to pedagogical approaches designed to help students develop 21C skills. These are typically social constructivist in nature and often involve students collaborating to complete challenging project work. These approaches can be used within formal education but are often more prominent in programmes situated outside of the formal system. This is primarily because these programmes have the flexibility to help students gain relevant experience and skills, without the pressure of state examinations (Cort, 2014; Fullan & Langworthy, 2014). However, it is often difficult to determine the long-term impact of non-formal interventions due to short-term funding, turnover in staff or changes in programme objectives (Souto-Otero, Ulicna, Schaepkens, & Bognar, 2013). The evaluations associated with most non-formal education take place during, or soon after, the programme and rarely have the scope to use mixed methods in data collection (Decker, McGill, & Settle, 2016). The Bridge to College programme is a non-formal education initiative (Lawlor, Conneely, Oldham, Marshall, & Tangney, 2018) that was re-designed by the author to help students develop 21C skills and confidence. The Bridge21 pedagogical model is employed throughout the programme. Key features of the programme include working in small teams with students from other schools, completing creative technical projects, and presenting their work to their peers (Byrne, Kearney, & Sullivan, 2019). Students spend four days participating in the programme in a custom-designed learning space. The research questions in this thesis relate to understanding the impact that participation in this programme has on the 21C skills and confidence of the students (RQ1), exploring which features of the programme help create this impact (RQ1a), and examining whether this impact is sustained in the years after completing the programme (RQ2). An evaluative case study was carried out using a concurrent mixed-methods approach. This included the collection of quantitative and qualitative data from student surveys and group interviews, both before and immediately after participation in the programme and again between one and seven years later. The aim of collecting data at various time points was to determine whether there were measurable effects at the time of the programme and, if so, to determine whether these effects were temporary or had a meaningful long-term impact. From the quantitative data presented, students report large increases in confidence across a range of key skills following participation in the programme. Crucially, these effects remain visible several months after completing the programme. Students described learning new skills, becoming more comfortable around new people, and reduced nervousness about public speaking. The research shows that the development of these skill areas can be linked directly to aspects of the programme design. The longitudinal aspect of this study is of particular interest. The reported effects appear to be more than a temporary spike created by the novelty of the students experience. They are sustained and remain present over many years. In further surveys and interviews, up to seven years after participating in the programme, students reported that the boost in skills and confidence gained during their time on Bridge to College remained with them over a long period. The scope of the study was limited by the fact that most of the data collected were self-reported by students. Other limitations to acknowledge include personal bias, as the researcher was in a participant/observer role, and that students volunteering for some aspects of the longitudinal research were likely to be positively disposed towards the Bridge to College programme. There is strong evidence that the Bridge to College programme can provide increases in student confidence across a range of 21C skills. These increases are statistically significant with large effect sizes, and the increases can be linked to elements in the programme design. This impact has been shown to be long-lasting, remaining present in the months and years after students have completed the programme. The main contributions of this research, in the fields of 21C learning and non-formal education, are: i) The design of the Bridge to College programme, a non-formal education programme to promote 21C skills development. ii) A deeper understanding of whether, and how, this programme impacts 21C skills development. iii) An exploration of the long-term impact of this out-of-school, non-formal educational intervention.
APPROVED
Keywords: 21C Learning; 21C Skills; Social Constructivism; Non-Formal Education; Key Skills; Project Based Learning; Collaborative Learning